Response evaluation of SGLT2 inhibitor therapy in patients with type 2 diabetes mellitus using 18F-FDG PET/MRI. Issue 1 (22nd March 2020) - Rasul, Sazan; Geist, Barbara Katharina; Brath, Helmut; Baltzer, Pascal; Sundar, Lalith Kumar Shiyam; Pichler, Verena; Mitterhauser, Markus; Kautzky-Willer, Alexandra; Hacker, Marcus
Abstract : Introduction: Inhibitors of sodium-glucose linked transporter-2 (SGLT2i) are enhancing glucose excretion in the proximal renal tubules, and thus are increasingly used to lower blood glucose levels in patients with type 2 diabetes mellitus (T2DM). The glucose analog 2-deoxy-2-( 18 F) fluoro-D-glucose (FDG) can be used to quantify renal function in vivo, and due to an affinity for SGLT2 could also provide information about SGLT2 transporter function. Our objectives in this study were, therefore, to assess the impact of SGLT2i on renal function parameters in patients with T2DM and identify predictive parameters of long-term response to SGLT2i using dynamic FDG positron emission tomography (PET)/MRI. Methods: PET FDG renal function measures such as mean transit time (MTT) and general renal performance (GRP) together with glomerular filtration rate (GFR) were determined in 20 patients with T2DM before (T2DMbaseline ) and 2 weeks after initiation of therapy with SGLT2i (T2DMSGLT2i ). Additionally, dynamic FDG PET data of 24 healthy subjects were used as controls. Results: MTT in T2DMbaseline was significantly higher than in healthy controls (5.7 min vs 4.3 min, p=0.012) and significantly decreased to 4.4 min in T2DMSGLT2i (p=0.004). GRP of T2DMSGLT2i was higher than of T2DMbaseline (5.2 vs 4.7, p=0.02) and higher but not significantly than of healthy individuals (5.2 vs 5.1, p=0.34). Expectedly, GFR of healthy participants was significantly higher than of T2DMbaseline and T2DMSGLT2i (122 vs 92 and 86 mL/min/1.73 m², respectively; p<0.001). The higher the GRP value in kidneys of T2DMSGLT2i, the lower was the glycated hemoglobin level 3 months after therapy initiation. Conclusion: MTT and GRP values of patients with T2DM shifted significantly toward values of healthy control 2 weeks after therapy with SGLT2i begins. GRP in T2DMSGLT2i was associated with better long-term glycemic response 3 months after initiation of therapy. Trial registration number: NCT03557138 .